Long-standing basal cell carcinoma of the nasal wing in an elderly female - Méndez, María José Ocejo; Treviño Flores, Jimena Celeste; Bermudez, Ulises Solis; Mateo, Carlos Ronaldo Martínez; Luna, Carla Andrea Amaya; Leal, Benjamín Jesús Moya; Navarro, Sylvana Cruz; Pérez, Imery Arlet Pérez (International Surgery Journal, 2025)
This case report describes a 75-year-old female with a long-standing basal cell carcinoma (BCC) of the left nasal wing, which had been present for approximately ten years. The lesion was characterized by a pigmented, irregular, plaque-like appearance with telangiectasias, and diagnosis was confirmed by biopsy. Surgical excision with reconstruction was planned to achieve complete tumor removal and restore nasal function. Managing BCC in the nasal area requires careful consideration to prevent potential complications such as tissue destruction, cartilage or bone invasion, and functional impairments, including nasal obstruction. The importance of early detection and the utilization of Mohs micrographic surgery as the preferred treatment option for high-risk or long-standing BCCs in cosmetically sensitive regions are emphasized. Long-term follow-up is crucial to detect recurrences and new skin malignancies, ensuring optimal outcomes.